The Effect of Tillage Treatments on Soil Temperature at Planting and on Corn (Zea mays L.) Yield - Pakurár, Miklós; Lakatos, László; Nagy, János (Acta Agraria Debreceniensis, 2001)
The effect of soil temperature was evaluated on the yield of the Occitan corn hybrid at a depth of 5 cm. We examined this effect on the time required from planting to emergence for three average durations: five, ten and fifteen days, all calculated from the day of planting. Winter plowing (27 cm), spring plowing (23 cm), disc-till (12 cm) treatments and 120 kg N per hectare fertilizer were applied. As a result of our analysis, we determined the post planting optimum soil temperatures for various time periods. The average soil temperature for a time period of 15 days post planting is the most usable for determining actual yields, followed by ten days, with five days proved to be the least usable (winter plow R2 = 0.86, spring plow R2 = 0.87, disc-till R2 = 0.64).